Emission and biosynthesis of volatile terpenoids from the plasmodial slime mold Physarum polycephalum - Chen, Xinlu; Köllner, Tobias G.; Xiong, Wangdan; Wei, Guo; Chen, Feng (Beilstein Journal of Organic Chemistry, 2019)
Terpene synthases (TPSs) are pivotal enzymes for the production of diverse terpenes, including monoterpenes, sesquiterpenes, and diterpenes. In our recent studies, dictyostelid social amoebae, also known as cellular slime molds, were found to contain TPS genes for making volatile terpenes. For comparison, here we investigated Physarum polycephalum, a plasmodial slime mold also known as acellular amoeba. Plasmodia of P. polycephalum grown on agar plates were found to release a mixture of volatile terpenoids consisting of four major sesquiterpenes (α-muurolene, (E)-β-caryophyllene, two unidentified sesquiterpenoids) and the monoterpene linalool. There were no qualitative differences in terpenoid composition at two stages of young plasmodia. To understand terpene biosynthesis, we analyzed the transcriptome and genome sequences of P. polycephalum and identified four TPS genes designated PpolyTPS1–PpolyTPS4. They share 28–73% of sequence identities. Full-length cDNAs for the four TPS genes were cloned and expressed in Escherichia coli to produce recombinant proteins, which were tested for sesquiterpene synthase and monoterpene synthase activities. While neither PpolyTPS2 nor PpolyTPS3 was active, PpolyTPS1 and PpolyTPS4 were able to produce sesquiterpenes and monoterpenes from the respective substrates farnesyl diphosphate and geranyl diphosphate. By comparing the volatile profile of P. polycephalum plasmodia and the in vitro products of PpolyTPS1 and PpolyTPS4, it was concluded that most sesquiterpenoids emitted from P. polycephalum were attributed to PpolyTPS4. Phylogenetic analysis placed the four PpolyTPSs genes into two groups: PpolyTPS1 and PpolyTPS4 being one group that was clustered with the TPSs from the dictyostelid social amoeba and PpolyTPS2 and PpolyTPS3 being the other group that showed closer relatedness to bacterial TPSs. The biological role of the volatile terpenoids produced by the plasmodia of P. polycephalum is discussed.
Keywords: amoebae; evolution; terpene synthases; volatiles

(untitled) - Chen, F.; Ludwiczuk, A.; Wei, G.; Chen, X.; Crandall-Stotler, B.; Bowman, J. L. (Crit. Rev. Plant Sci., 2018)

(untitled) - Schulz, S.; Dickschat, J. S. (Nat. Prod. Rep., 2007)

(untitled) - Audrain, B.; Farag, M. A.; Ryu, C.-M.; Ghigo, J.-M. (FEMS Microbiol. Rev., 2015)

(untitled) - Schulz-Bohm, K.; Geisen, S.; Wubs, E. R. J.; Song, C.; de Boer, W.; Garbeva, P. (ISME J., 2017)

(untitled) - Hung, R.; Lee, S.; Bennett, J. W. (Appl. Microbiol. Biotechnol., 2015)

(untitled) - Schmidt, R.; Etalo, D. W.; de Jager, V.; Gerards, S.; Zweers, H.; de Boer, W.; Garbeva, P. (Front. Microbiol., 2016)

(untitled) - McGenity, T. J.; Crombie, A. T.; Murrell, J. C. (ISME J., 2018)

(untitled) - Wisecaver, J. H.; Slot, J. C.; Rokas, A. (PLoS Genet., 2014)

(untitled) - Lichtenthaler, H. K. (Annu. Rev. Plant Physiol. Plant Mol. Biol., 1999)

(untitled) - Sapir-Mir, M.; Mett, A.; Belausov, E.; Tal-Meshulam, S.; Frydman, A.; Gidoni, D.; Eyal, Y. (Plant Physiol., 2008)

(untitled) - Lombard, J.; Moreira, D. (Mol. Biol. Evol., 2011)

(untitled) - Nagel, R.; Schmidt, A.; Peters, R. J. (Planta, 2019)

(untitled) - Chen, F.; Tholl, D.; Bohlmann, J.; Pichersky, E. (Plant J., 2011)

(untitled) - Chen, X.; Köllner, T. G.; Jia, Q.; Norris, A.; Santhanam, B.; Rabe, P.; Dickschat, J. S.; Shaulsky, G.; Gershenzon, J.; Chen, F. (Proc. Natl. Acad. Sci. U. S. A., 2016)

(untitled) - Chen, X.; Köllner, T. G.; Shaulsky, G.; Jia, Q.; Dickschat, J. S.; Gershenzon, J.; Chen, F. (Sci. Rep., 2018)

(untitled) - Rabe, P.; Rinkel, J.; Nubbemeyer, B.; Köllner, T. G.; Chen, F.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2016)

(untitled) - Yamada, Y.; Kuzuyama, T.; Komatsu, M.; Shin-ya, K.; Omura, S.; Cane, D. E.; Ikeda, H. (Proc. Natl. Acad. Sci. U. S. A., 2015)

Biotechnology of Isoprenoids - Schmidt-Dannert, C. (Biosynthesis of Terpenoid Natural Products in Fungi, 2014)

(untitled) - Alim, K.; Andrew, N.; Pringle, A.; Brenner, M. P. (Proc. Natl. Acad. Sci. U. S. A., 2017)

(untitled) - Taylor, B.; Adamatzky, A.; Greenman, J.; Ieropoulos, I. (BioSystems, 2015)

(untitled) - Bonifaci, V.; Mehlhorn, K.; Varma, G. (J. Theor. Biol., 2012)

(untitled) - Nakagaki, T.; Yamada, H.; Tóth, Á. (Nature, 2000)

(untitled) - Kateb, H. a.; Costello, B. d. L. (arXiv, 2013)

(untitled) - Schaap, P.; Barrantes, I.; Minx, P.; Sasaki, N.; Anderson, R. W.; Bénard, M.; Biggar, K. K.; Buchler, N. E.; Bundschuh, R.; Chen, X.; Fronick, C.; Fulton, L.; et al. (Genome Biol. Evol., 2016)

(untitled) - Driller, R.; Janke, S.; Fuchs, M.; Warner, E.; Mhashal, A. R.; Major, D. T.; Christmann, M.; Brück, T.; Loll, B. (Nat. Commun., 2018)

(untitled) - Jia, Q.; Chen, X.; Köllner, T. G.; Rinkel, J.; Fu, J.; Labbé, J.; Xiong, W.; Dickschat, J. S.; Gershenzon, J.; Chen, F. (Sci. Rep., 2019)

(untitled) - Rasmann, S.; Köllner, T. G.; Degenhardt, J.; Hiltpold, I.; Toepfer, S.; Kuhlmann, U.; Gershenzon, J.; Turlings, T. C. J. (Nature, 2005)

(untitled) - Köllner, T. G.; Held, M.; Lenk, C.; Hiltpold, I.; Turlings, T. C. J.; Gershenzon, J.; Degenhardt, J. (Plant Cell, 2008)

(untitled) - Chen, X.; Luck, K.; Rabe, P.; Dinh, C. Q.; Shaulsky, G.; Nelson, D. R.; Gershenzon, J.; Dickschat, J. S.; Köllner, T. G.; Chen, F. (eLife, 2019)

(untitled) - Dussutour, A.; Latty, T.; Beekman, M.; Simpson, S. J. (Proc. Natl. Acad. Sci. U. S. A., 2010)

(untitled) - de Lacy Costello, B. P.; Adamatzky, A. I. (Commun. Integr. Biol., 2013)

(untitled) - Suckling, D. M.; Stringer, L. D.; Bunn, B.; El-Sayed, A. M.; Vander Meer, R. K. (J. Chem. Ecol., 2010)

(untitled) - Adamatzky, A. (Parallel Process. Lett., 2009)

(untitled) - Romeo, A.; Dimonte, A.; Tarabella, G.; D’Angelo, P.; Erokhin, V.; Iannotta, S. (APL Mater., 2015)

(untitled) - Tero, A.; Kobayashi, R.; Nakagaki, T. (J. Theor. Biol., 2007)

(untitled) - Tsuda, S.; Aono, M.; Gunji, Y.-P. (BioSystems, 2004)

(untitled) - Haas, B. J.; Papanicolaou, A.; Yassour, M.; Grabherr, M.; Blood, P. D.; Bowden, J.; Couger, M. B.; Eccles, D.; Li, B.; Lieber, M.; MacManes, M. D.; Ott, M.; et al. (Nat. Protoc., 2013)

(untitled) - Jia, Q.; Li, G.; Köllner, T. G.; Fu, J.; Chen, X.; Xiong, W.; Crandall-Stotler, B. J.; Bowman, J. L.; Weston, D. J.; Zhang, Y.; Chen, L.; Xie, Y.; et al. (Proc. Natl. Acad. Sci. U. S. A., 2016)

(untitled) - Finn, R. D.; Clements, J.; Eddy, S. R. (Nucleic Acids Res., 2011)

(untitled) - Katoh, K.; Standley, D. M. (Mol. Biol. Evol., 2013)

(untitled) - Price, M. N.; Dehal, P. S.; Arkin, A. P. (Mol. Biol. Evol., 2009)

(untitled) - Li, G.; Köllner, T. G.; Yin, Y.; Jiang, Y.; Chen, H.; Xu, Y.; Gershenzon, J.; Pichersky, E.; Chen, F. (Proc. Natl. Acad. Sci. U. S. A., 2012)